Neighborhood, community and consumption: Study on the socio-spatial structure during two boosting epochs in Shanghai - Xiang Zhou; Yanbo Li; Yuning Cheng (Frontiers of Architectural Research, 2020)
The modernization of Shanghai has experienced two boosting periods. The first appeared in the 1930s, when it formed the civil society of Shanghai and initially facilitated the trade port into an international metropolis. The second started after the nation's reform and opening-up, which attempted to promote the city into a global metropolis in the 2010s. In order to evaluate the socio-spatial transitions of communities in Shanghai during the process, Lilong historical neighborhoods in the 1930s and 2010s are successively chosen as research objects. Meanwhile, three specific neighborhoods in each period are selected for case study, so as to depict different symbiosis patterns of the socio-spatial structures under different spatiotemporal conditions by means of a cross-sectional analysis of the consumption level. By pointing out Shanghai in the 1930s was marked with social integration and local-based consumption, while it was inundated with administration tendency and global-oriented consumption in the 2010s, the article believes the dual integration of local-based and global-oriented consumptions is an alternative solution for Shanghai. Finally, the article proposes that Shanghai's current urban regeneration should rely on the multi-centered symbiotic structure to create a compound network, during which territorial socio-spatial structures and basic living needs of the plebeian can be simultaneously preserved.